Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1139/cjfr-2013-0488
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the effects of liming and wood-ash treatment on forest ecosystems through systematic meta-analysis

Abstract: Liming and wood-ash addition have long been used to attenuate the effects of acidic deposition on forest soils with the goal of promoting tree growth. We performed quantitative meta-analyses of treatment studies from managed forest ecosystems to assess general tendencies of effects of treatment on seven selected measures of performance thought to reasonably reflect the effects of Ca-addition treatment. We retrieved over 350 independent trials from 110 peer-reviewed liming and wood-ash addition studies that wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
85
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(93 citation statements)
references
References 90 publications
7
85
0
1
Order By: Relevance
“…Our estimated lime requirement did not differ among the three watersheds we studied. However, as reported in the literature (Reid and Watmough, 2014), riparian zone soils which have greater organic C content, required less lime to increase soil pH to 5.5. Understanding stream acidity responses to riparian zone or catchment level liming would require experimental lime addition, ideally in catchments with the low extractable Ca and high stream acidity such as, those in the Santeetlah Creek watershed.…”
Section: Catchment Liming and Mitigationmentioning
confidence: 51%
See 2 more Smart Citations
“…Our estimated lime requirement did not differ among the three watersheds we studied. However, as reported in the literature (Reid and Watmough, 2014), riparian zone soils which have greater organic C content, required less lime to increase soil pH to 5.5. Understanding stream acidity responses to riparian zone or catchment level liming would require experimental lime addition, ideally in catchments with the low extractable Ca and high stream acidity such as, those in the Santeetlah Creek watershed.…”
Section: Catchment Liming and Mitigationmentioning
confidence: 51%
“…Lime contains Ca and Mg, the two major divalent base cations; the ratio of these cations is dependent on the lime sources. Huettl (1993) and more recently Reid and Watmough (2014) review benefits and problems of lime applications in forest liming studies. The meta-analysis conducted by Reid and Watmough (2014) found that 67% of lime treatment trials showed increased soil pH and foliar Ca concentration.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Wildfire is the dominant stand-replacing disturbance across large regions of the country but the chemical effects of wildfire on soil properties are difficult to emulate (McRae et al 2001). Both wildfires and applications of wood ash typically increase surface soil pH and base cation availability (Bodí et al 2014, Reid andWatmough 2015) but there has been little work to directly compare the response of soil properties and processes to these two types of disturbance (Noyce et al 2016). To this end, AshNet collaborators are conducting a formal meta-analysis to statistically compare changes in soil chemical properties following wildfire and wood ash applications.…”
Section: Examining Wood Ash Applications As a Tool For Emulating Natumentioning
confidence: 99%
“…Numerous studies have demonstrated that applications of wood ash on forest soils can be used to replace some of the nutrients, e.g., phosphorus (P), calcium (Ca), magnesium (Mg), potassium (K) removed during timber harvesting; counteract the effects of acid rain on forest soils and surface water bodies; and, improve tree growth (Pitman 2006, Huotari et al 2015, Reid and Watmough 2015. In some European countries, applications of wood ash are encouraged to prevent nutrient deficiencies following biomass harvesting, particularly on nutrient-poor forest sites (Karltun et al 2008, Forestry Commission 2009.…”
Section: Introductionmentioning
confidence: 99%